Severe Dizziness Related to Postural Instability, Changes in Gait and Cognitive Skills in Patients with Chronic Peripheral Vestibulopathy - Coelho, Almir Resende; Perobelli, Júlia Licursi Lambertti; Sonobe, Lilian Shizuka; Moraes, Renato; Barros, Camila Giacomo de Carneiro; Abreu, Daniela Cristina Carvalho de (International Archives of Otorhinolaryngology, 2020)
Introduction Peripheral vestibular disorders can lead to cognitive deficits and are more common in elderly patients.Objective To evaluate and correlate cognitive, balance and gait aspects in elderly women with chronic peripheral vestibular dizziness, and to compare them with elderly women without vestibular disorders.Methods Twenty-two women presenting peripheral vestibular dizziness episodes for at least six months participated in the study. The individuals were categorized by dizziness severity level: moderate (n = 11) or severe (n = 11). The control group (n = 11) included women showing no vestibulopathy, light-headedness or dizziness. Cognitive assessments and semi-static and dynamic balance assessments were performed with the Balance Master (Neurocom International, Inc., Clackamas, OR), while the Dizziness Handicap Inventory provided a score for the severity of the symptoms. The groups were submitted to statistics of inference and correlation between cognitive, balance and stability variables.Results The group with severe dizziness showed higher sway speed of the center of pressure in the anteroposterior direction, smaller step length, and slower gait than the control group. Regarding the cognitive variables, the group with severe dizziness symptoms presented significant correlations with stability and gait variables.Conclusion The relationship between cognitive aspects, balance and gait was stronger in women with severe dizziness than in those with no vestibulopathy.
Keywords: vestibular diseases; aging; dizziness; rehabilitation